A double blind, randomised placebo controlled trial of rifampicin with omeprazole in the treatment of human cutaneous leishmaniasis - D.K. Kochar, Govind Saini, S.K. Kochar, P. Sirohi, R.A. Bumb, R.D. Mehta,S.K. Purohit (Journal of Vector Borne Diseases, 2006)
Background & objectives: This study was conducted on 50 patients of Anthroponotic cutaneousleishmaniasis (oriental sore) to assess the efficacy of rifampicin and omeprazole through a doubleblind, randomised placebo control study.Methods: The diagnosis of Anthroponotic cutaneous leishmaniasis (ACL) caused by Leishmania tropicawas done by demonstration of Leishmania tropica (LT) bodies from the painless, dry ulcerative lesion.Each patient was assessed clinically in the beginning of the study, at the end of 2 ,4 and 6 weeks andall observations were compared in both the groups. Twenty-five patients received rifampicin withomeprazole (Group A) whereas other 25 patients received placebo (Group B) for a period of six weeks.Results: Altogether 23 cases in group A and 21 cases in group B completed the study. About 16 (69.7%)cases in group A and 3 (14.29%) cases in group B had complete healing, whereas 3 patients (13.04%)of group A and 4 patients (19.05%) of group B had partial response and 4 patients (17.93%) of groupA and 14 patients (66.67%) of group B had no response at the end of study. The difference of twogroups was statistically highly significant (p<0.00025). All patients tolerated the drug and placebo verywell and no side effect was reported.Interpretation & conclusion: In our opinion rifampicin and omeprazole is a highly effective, less toxicand cheaper alternative for the management of cutaneous leishmaniasis.